Bioprinting Tissue Analogues with Decellularized Extracellular Matrix Bioink for Regeneration and Tissue Models of Cartilage and Intervertebral Discs. (11th June 2020) - Vernengo, Andrea J.; Grad, Sibylle; Eglin, David; Alini, Mauro; Li, Zhen
Abstract: The recent convergence of decellularized extracellular matrix (dECM) methodologies and 3D bioprinting (3DBP) has led to multiple advancements in tissue engineering scaffold design by enabling researchers to recreate a tissue‐specific 3D environment in a custom geometry. The application of 3DBP of dECM for articular cartilage and intervertebral disc (IVD) repair, however, is still burgeoning. While cartilage and IVD tissue each possess unique architectures, they are composed of similar macromolecules and therefore pose similar challenges for the successful application of their matrix bioinks. Herein, the state‐of‐the‐art in cartilage and IVD dECM bioink preparation, material properties, and applications are highlighted. The current major obstacles regarding optimal decellularization and printing methods are discussed, which need to be overcome to enable recapitulation of the hierarchical organization, zone‐specific matrix composition, and anisotropic biomechanical behavior of the native tissues. Finally, a vision is presented for how this field may continue to evolve in the future to empower the fabrication of scaffolds that serve as effective templates for guiding cellular assembly and organization toward the formation of functional cartilage and IVD tissues. Abstract : This progress report summarizes the state‐of‐the‐art in cartilage and intervertebral disc (IVD) decellularized extracellular matrices bioink preparation and 3D bioprinting applications, and discusses the future perspectives in this field to empower the fabrication of scaffolds that serve as effective templates for guiding cellular assembly and organization toward the formation of functional cartilage and IVD tissues.